Psychiatric health of Icelandic adults 40 years or older: A nationwide study of diagnoses, medications, and symptoms - Inga Wessman; Lauren P. Wadsworth; Lárus Steinþór Guðmundsson; Þorvarður Jón Löve; Sæmundur Rögnvaldsson; Guðmundur Bjarni Arnkelsson; Andri Ólafsson; Sigrún Þorsteinsdóttir; Björn Leví Gunnarsson; Guðrún Ásta Sigurðardóttir; Nicholas J. Sibrava; Ásdís Rósa Þórðardóttir; et al. (PLoS ONE, 2026)
Nationwide, population-based psychiatric health data, preferably incorporating information from various assessment methods such as health registries and self-report measures, are needed to manage healthcare systems and shape public health policies. The aim of the study is to assess the psychiatric health of individuals 40 years and older by examining data on psychiatric diagnoses, medication, anxiety and depressive symptoms, and life satisfaction. This is a cross-sectional study using a nationwide cohort. All Icelanders 40 years and older were invited to participate in this cross-sectional study, and 80,759 (54.3%) registered. Data from health registries and validated self-report measures were used. A total of 16,764 individuals (20.8%) received one or more psychiatric diagnoses in the year prior to starting the study, with nonorganic sleep disorders, other anxiety disorders, and a depressive episode being the most common. Additionally, 27,642 (34.2%) filled at least one psychotropic prescription (19.9% without a formal diagnosis filled prescriptions), with 24.3% filling one or more prescriptions for benzodiazepine related medications or benzodiazepine derivatives. Rates of diagnoses and filled prescriptions increased across age groups. Most participants reported no or mild anxiety (94.3%), and minimal or mild depressive symptoms (88.8%). Over half (59.3%) reported satisfaction or extreme satisfaction with life. The results reveal the widespread prevalence of psychiatric disorders across the population in a real-world, nationwide context, emphasizing the need for psychiatric care. However, the non-specific and broad nature of diagnoses limits the ability to provide appropriate care. Additionally, the findings highlight a reliance on psychotropic medications to manage psychiatric symptoms and disorders, even without a formal diagnosis. The rate of filled benzodiazepine prescriptions is alarming, as these medications are not recommended as a first-line treatment for psychiatric disorders. The findings provide population-based psychiatric health data that can inform healthcare management and guide public health policy.